ANALISIS KETERAMPILAN BERPIKIR KRITIS MURID PADA MATERI GAYA KELAS IV SDN TEGAL BESAR 02 JEMBER - Nur Illah Merdiana; Mely Agustin Reni Pitasari; Prima Cristi Crismono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study analyzes elementary students' critical thinking skills on force material based on Ennis's indicators, identifying the highest and lowest indicators and influencing factors. A mixed method with sequential explanatory design was employed. Subjects were 20 fourth-grade students at SDN Tegal Besar 02. The instrument was a 10-item essay test based on five Ennis indicators: elementary clarification, basic support, inference, advanced clarification, and strategy and tactics. Quantitative data were analyzed using percentages, while qualitative data from teacher interviews enriched the findings. Results showed students' average critical thinking ability was in the medium category (46.8%). The elementary clarification indicator achieved the highest percentage (56%, medium category), with students able to analyze arguments and provide simple explanations. Conversely, the strategy and tactics indicator obtained the lowest percentage (37%, low category) as students struggled to determine strategies and plan actions logically due to lack of problem-solving practice. The relationship between indicators is gradual, where basic clarification serves as a foundation but does not automatically improve strategic skills without learning that encourages independent problem-solving.